2017
DOI: 10.1155/2017/5816263
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Brain Functional Connectivity Changes of the Cortical Motor-Related Network in Subcortical Stroke Patients with Acupuncture Treatment

Abstract: In clinical practice, the effectiveness of the rehabilitation therapy such as acupuncture combining conventional Western medicine (AG) on stroke people's motor-related brain network and their behaviors has not been systematically studied. In the present study, seventeen adult ischemic patients were collected and divided into two groups: the conventional Western medicine treatment group (CG) and the AG. The neurological deficit scores (NDS) and resting-state functional MRI data were collected before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…Ones are based on conventional therapy. For example, Li et al observed increased functional connectivity of acupuncture in addition to western medicine group from pre- and posttreatment for stroke [12]. The others compared either the differences of functional brain activities changes between acupoints combination and sham acupoints on patients [13] or acupoints combination manipulation on patients and the healthy controls [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Ones are based on conventional therapy. For example, Li et al observed increased functional connectivity of acupuncture in addition to western medicine group from pre- and posttreatment for stroke [12]. The others compared either the differences of functional brain activities changes between acupoints combination and sham acupoints on patients [13] or acupoints combination manipulation on patients and the healthy controls [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture could modulate interhemispheric and intrahemispheric FC among multiple cortical motor areas, implicating brain plasticity in the motor-related network in a stroke with a unilateral subcortical lesion [58, 59]. For instance, acupuncture intervention can improve declined FC between the bilateral M1 in stroke patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Central integration has been considered as an essential mechanism acupuncture's therapeutic effect since the 1970s [27,28]. In the past 20 years, with the aid of functional brain imaging techniques such as fMRI, positron emission tomography, electroencephalography, and magnetoencephalography [29], investigators have mapped the cerebral regions/circuits/networks participating in acupuncture effects for treating neuropathies [30][31][32][33], gastrointestinal disorders [34][35][36], and motor diseases [37,38]. These studies provided abundant visual evidence for understanding the central mechanism of acupuncture.…”
Section: Study Feasibilitymentioning
confidence: 99%